Therapeutic efficacy of metronomic chemotherapy with cyclophosphamide and doxorubicin on murine mammary adenocarcinomas - Mainetti, Leandro Ernesto (2013)
Fil: Fil: Mainetti, Leandro Ernesto. Institute of Experimental Genetics. School of Medical Sciences. National University of Rosario; Argentina